Potential of Archeotourism at the Megalithic Site in Pengkalan Kempas Historical Complex, Negeri Sembilan: An Analysis of Community Perception - Ibrahim, Nurfatin; Ramli, Zuliskandar; Mahadzir, Sri Yanti; Ahmad, Shamsuddin (Journal of Ecohumanism, 2025)
Archeotourism is a new branch of the tourism industry in Malaysia that is rarely promoted to the local community. This sector is more focused on tourism based on archaeological heritage sites which can generate significant income for the state. These archaeotourism-based heritage sites are found throughout the country but do not receive as encouraging a reception from tourists as the Megalithic Sites in Negeri Sembilan. The objective of this study is to determine the local community’s perception of the existence of this megalithic site because this megalithic stone needs to be preserved and maintained so that it becomes one of the archaeotourism products to elevate this prehistoric stone as an archaeological heritage site comparable to the discovery of the Sungai Batu civilization site. Therefore, this study uses a quantitative method approach involving as many as 400 respondents consisting of local residents and tourists using research question instruments and the results of the study will be processed using SPSS version 26. The research conducted has shown that while these sites have significant historical and cultural value, public and domestic tourist awareness and understanding of the megalithic sites are still limited. This indicates that there is ample room for education and promotion to enhance recognition of this heritage. Through this study, megalithic sites are identified not only as archaeological heritage sites but also as semiotic canvases that reflect the rich culture and history of the Minangkabau community. This is the impact of this study, the archaeotourism industry will be given attention and awareness to the public in order to preserve archaeological sites, especially to promote the existence of megalithic sites because this industry has great potential on a global scale and is able to generate significant income for the country.